Effects of conventional and alternative asthma therapies on the GIT and heart in an experimental model of murine asthma - warrenv@live.co.za (University of Pretoria, 2013)
Dissertation (MSc (Anatomy with specialization in Cell Biology))--University of Pretoria, 2010.